678 WIDE COMPLEX TACHYCARDIA IN A PATIENT TREATED WITH PERMANENT HIS BUNDLE PACING: A CASE REPORT. (15th December 2022) - Rizzello, Davide; FrancescaNotarangelo, Maria; Bearzot, Luca; Crocamo, Antonio; Gonzi, Gianluca; Dinatale, Alessandro; Grassi, Francesca; Niccoli, Giampaolo; Ardissino, Diego
Abstract: Introduction: Differential diagnosis of wide complex tachycardias based only on ECG analysis remains a challenging exercise. But, when intracardiac tracings are available (i.e., pacemaker EGM), electrophysiologists may consider several tricks to make a correct diagnosis. Case Presentation: A 73-years-old sporty male was admitted to our hospital for palpitations and dizziness. ECG monitoring revealed AF, typical atrial flutter and asystolic pauses following spontaneous cardioversion of atrial arrhythmias. We diagnosed sick sinus syndrome and implanted a dual-chamber pacemaker with an atrial lead in the right appendage and a stylet-directed active fixation lead in the His region, obtaining non-selective narrow paced QRS. The day after PM implantation, during a new episode of AF, two runs of regular wide-complex tachycardia (LBBB morphology, cycle length of 270 ms) occurred (Fig 1A, B). LBBB morphology, patient's history, and AF favored aberrancy, but couldn't exclude VT or preexcitation (by atrio-fascicular AP). Our diagnostic strategy consisted in adding atrial and His intracardiac electrograms registered by pacemaker to analysis of ECG traces. The device interrogation showed AV dissociation at the time of the wide complex tachyarrhythmia and a negative HV interval (Fig. 2A). These findings ruled out aberrant ventricular conduction and bundle branch reentrant tachycardia, because both these arrhythmias are characterized by HV ≥ HV in sinus rhythm. We performed incremental atrial pacing maneuver, during SR, obtaining decremental AH conduction with constant HV interval (60 ms), excluding atrio-fascicular, nodo-fascicular and nodo-ventricular AP. His bundle activity was identified just after the ventricular activation, producing a relatively short VH interval, suggesting the presence of a retrograde activation of the His bundle, therefore it was possible to hypothesize that the site of origin of the ventricular arrhythmia was within/or very close to RBB (Fig 2B, C). Just in few beats His bundle deflection was missing, probably because of recovery of functional LBBB (Fig 2D). Discussion: Our final diagnosis was RBB VT. Patient was treated with Verapamil 80 mg t.i.d., with no further recurrence. This case highlights the diagnostic value of device interrogation in patients with permanent His bundle pacing, for the evaluation of wide complex tachycardias.